Experience With a Care Process Model in the Evaluation of Pediatric Musculoskeletal Infections in a Pediatric Emergency Department. Issue 9 (September 2019) - Patel, Lina; Michael, Jeff; Allen, Nancy; Schroeder, Lisa; Berglund, Lisa; Newland, Jason G.
Abstract : Objectives: Care process models (CPMs) for certain conditions have improved clinical outcomes in children. This study describes the implementation and impact of a CPM for the evaluation of musculoskeletal infections in a pediatric emergency department (ED). Methods: A retrospective pre-post intervention study was performed to analyze the impact of a musculoskeletal infection CPM. Patients were identified retrospectively through electronic order history for imaging of an extremity or joint and recommended laboratory tests. Clinical outcomes evaluated included hospital length of stay (LOS), time to magnetic resonance imaging (MRI), time to administration of antibiotics, hospital admission rate, and 30-day readmission rate. Results: Musculoskeletal infection evaluations completed in the ED were reviewed from 1 year before implementation (n = 383) and 2 years after implementation (n = 1219) of the CPM. A significant improvement in the time to antibiotic administration for all patients (4.3 vs 3.7 hours, P < 0.05) and for patients with confirmed musculoskeletal infections (9.5 vs 4.9 hours, P < 0.05) was observed after the implementation of the CPM. The overall time to MRI (13.2 vs 10.3 hours, P = 0.29) and hospital LOS (4.7 vs 3.7 days, P = 0.11) were improved for all patients but were not statistically significant. The admission rate and 30-day readmission were similar before and after the implementation of the CPM. Conclusions: The implementation of a musculoskeletal infection CPM has standardized the approach to the evaluation and diagnosis of musculoskeletal infections resulting in a significant decrease in the time to administer antibiotics and a downward trend in time to MRI and hospital LOS. Abstract : Supplemental digital content is available in the text.